Multiple assessment in large-scale river basins (Research, Society and Development, 2022)
The knowledge of morphometry, relief and drainage network of hydrographic basins is important for environmental management. Therefore, this study aims to characterize the morphometry and identify the relief characteristics in nine hydrographic basins tributary of the Iguaçu River. The characterization of slopes, drainage network and slope was performed using a Digital Terrain Model (DTM) and the data obtained were visually compared to the results of the topographic maps of the National Water Agency (ANA) (2015). The analyzed basins presented in general elongated shapes, being little susceptible to floods, with undulating relief, with intermediate to poor drainage and sinuosity from intermediate to high. The results obtained are similar to those obtained by ANA (2015), based on smaller scales. The hierarchies for each basin were satisfactory, as well as the methodology used, as it does not require the use of sophisticated machines for its execution, and results in reliable data with little loss of precision. The results are unprecedented for these basins and the estimated geomorphological variables can support decision making both in relation to the risks of anthropic activities and the definition of conservation areas, especially areas of interest for the conservation of water and aquatic ecosystems.